2021
DOI: 10.1186/s12935-021-02079-4
|View full text |Cite
|
Sign up to set email alerts
|

PCAT6 may be a new prognostic biomarker in various cancers: a meta-analysis and bioinformatics analysis

Abstract: Background LncRNA prostate cancer-associated transcript 6 (PCAT6) has been reported to be dysregulated in several cancers and is associated with tumor progression. Here, we have performed a meta-analysis to assess the general prognostic role of PCAT6 in malignancies. Methods Four public databases (Embase, Pubmed, Web of Science, Cochrane Library) were used to identify eligible studies, then data was extracted and associations between prognostic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For instance, prostate cancer-associated transcript 6 (PCAT6) was significantly increased in various cancers. The overexpression of PCAT6 was closely correlated with OS, TNM stage, distant metastasis, LNM, tumor size, and the degree of differentiation in cancer patients ( Shi et al, 2021 ), which may be a new cancer-related biomarker. In recent years, numerous studies found that the HOXA-AS2 was overexpressed in a variety of tumor types, such as CC ( Chen and He, 2021 ), OSCC ( Chen et al, 2021 ), PCa ( Xiao and Song, 2020 ) and so on.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, prostate cancer-associated transcript 6 (PCAT6) was significantly increased in various cancers. The overexpression of PCAT6 was closely correlated with OS, TNM stage, distant metastasis, LNM, tumor size, and the degree of differentiation in cancer patients ( Shi et al, 2021 ), which may be a new cancer-related biomarker. In recent years, numerous studies found that the HOXA-AS2 was overexpressed in a variety of tumor types, such as CC ( Chen and He, 2021 ), OSCC ( Chen et al, 2021 ), PCa ( Xiao and Song, 2020 ) and so on.…”
Section: Discussionmentioning
confidence: 97%
“…Despite being an inert tumor that possesses a high overall survival (OS) rate, PCa progresses rapidly after the turning point of recurrence, even with the available clinical interventions (8). Thus, consistent with other PCa prognostic studies (38)(39)(40)(41)(42), DFS was selected as the endpoint of this study.…”
Section: Discussionmentioning
confidence: 98%
“…LncRNA CRNDE was identified as an oncogenic lncRNA and involved in tumor growth and metastasis ( 21 - 23 ). A growing body of research has shown PCAT6 playing key roles in many different cancers, with the upregulation of this lncRNA being associated with worse prognostic outcomes and clinical features, underscoring its promising utility as a prognostic biomarker ( 24 ). For example, one study of osteosarcoma samples revealed higher PCAT6 expression in these tumors relative to paracancerous normal bone tissue, with such upregulation being linked to worse patient survival and a more malignant phenotype ( 25 ).…”
Section: Discussionmentioning
confidence: 99%